Advances in Polysaccharide- and Synthetic Polymer-Based Vitreous Substitutes - Kruti Naik; Lisa C. Du Toit; Naseer Ally; Yahya E. Choonara (MDPI AG, 2023)
The vitreous humour is a gel-like structure that composes the majority of each eye. It functions to provide passage of light, be a viscoelastic dampener, and hold the retina in place. Vitreous liquefaction causes retinal detachment and retinal tears requiring pars plana vitrectomy for vitreous substitution. An ideal vitreous substitute should display similar mechanical, chemical, and rheological properties to the natural vitreous. Currently used vitreous substitutes such as silicone oil, perfluorocarbon liquids, and gases cannot be used long-term due to adverse effects such as poor retention time, cytotoxicity, and cataract formation. Long-term, experimental vitreous substitutes composed of natural, modified and synthetic polymers are currently being studied. This review discusses current long- and short-term vitreous substitutes and the disadvantages of these that have highlighted the need for an ideal vitreous substitute. The review subsequently focuses specifically on currently used polysaccharide- and synthetic polymer-based vitreous substitutes, which may be modified or functionalised, or employed as the derivative, and discusses experimental vitreous substitutes in these classes. The advantages and challenges associated with the use of polymeric substitutes are discussed. Innovative approaches to vitreous substitution, namely a novel foldable capsular vitreous body, are presented, as well as future perspectives related to the advancement of this field.